Special issue: ‘Literacy, language and social justice in the changing university’ - Thesen, Lucia; Jacobs, Cecilia; Paxton, Moragh (Critical Studies in Teaching and Learning, 2023)
In  this  special  issue  we  share  insights  into  how  academics  understand  and  research  literacy and  language  in  the  context  of  calls  for  social  justice  rather  than(or  as  well  as)  throughput and  efficiency.  This  special  issue  comes  about  in  the  wake  of  a  crucial  moment  in  South African higher education, a moment of intense student led protest that has asked fundamental questions about what higher education is, who it is for, who it excludes. Not since the student led Soweto Uprising of 1976 have young people so insistently asked questions of the flawed educational inheritance that is coming their way. This questioning is not only taking place in South  Africa but  the local protests  have  an  added  urgency  and  meaning  because  of  the historical context –a  generation  after  apartheid,  inequality  is  still  sharply  etched  despite widening  participation.  Literacy  and  language  are  often  implicated  in  this  challenge  to business-as-usual, raising questions about knowledge, pedagogy and taken-for-granted forms. It  continues  to  be  a  crucial  topic  in  this  journal,  and  in  critical  approaches  to  teaching  and learning in higher education, in South Africa in particular with its post-colonial context where English is in one way or another always a borrowed language, and writing in English carries with it profound dilemmas about identity and being.